2015
DOI: 10.1177/0310057x1504300110
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Intra-Aortic Balloon Pump Use: Does the Final Position of the IABP Tip Matter?

Abstract: We report results of a retrospective review of intra-aortic balloon pump (IABP) use in two Australasian centres and evaluate the effect of final IABP tip position on outcome. Indications for counterpulsation, patient demographics and in-hospital outcomes and complications were retrospectively collected. The chest X-ray reports provided the 'final' position of the IABP tip. The position was defined as acceptable (tip was seen just below the aortic arch, at T2-T5 vertebrae), malpositioned (tip >5 cm below aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Studies of IABP to support PCI report bleeding rates of 3.3–8.4% [5355]. More recent studies of IABP for AMI, CS, UA, and perioperative use report rates from 0.8 to 26.3% [3335, 37, 39, 41, 56–60]. Bleeding rates for Impella ® are poorly described, but range from as low as 0.05% to 54% when inserted percutaneously [21, 44, 61–64].…”
Section: Complications Of Temporary Percutaneous Mechanical Circulatomentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of IABP to support PCI report bleeding rates of 3.3–8.4% [5355]. More recent studies of IABP for AMI, CS, UA, and perioperative use report rates from 0.8 to 26.3% [3335, 37, 39, 41, 56–60]. Bleeding rates for Impella ® are poorly described, but range from as low as 0.05% to 54% when inserted percutaneously [21, 44, 61–64].…”
Section: Complications Of Temporary Percutaneous Mechanical Circulatomentioning
confidence: 99%
“…Therefore, the assessment of neurological injury and development of CVA is complex in this population. CVA rate in IABP is typically low, 1–10% [35, 39, 42, 49, 52, 53, 55, 56, 58, 74, 75, 91]. Impella ® and TandemHeart ® have rates similar to IABP, reported from 2.4 to 6.3% [29, 65, 66, 82, 88].…”
Section: Complications Of Temporary Percutaneous Mechanical Circulatomentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptance of less-ideal placement of the balloon was indicative of the morbidity of the patient in most cases. 9 The primary complication is arterial damage from the catheter; however, ischemia of the limbs, thrombosis, renal failure, balloon leaks, vessel perforations, and bleeding are all possible complications that can arise. There are several recent studies done to show the effectiveness of the IABP.…”
Section: Intra-aortic Balloon Pumpmentioning
confidence: 99%
“…One study looking at IABP positioning showed a 13-fold increased risk of major complications, including renal failure and mesenteric ischemia, compared to a properly positioned IABP. 8 Although not mentioned in their study, hopefully the authors corrected IABP malposition (or even removed it), which should be demonstrated on postoperative radiologic exams.…”
mentioning
confidence: 90%